2009
DOI: 10.2190/hs.39.4.m
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up Global Social Health Protection: Prerequisite Reforms to the International Monetary Fund

Abstract: People living in low-income countries require protection from the economic and social impacts of global economic competition, yet, historically, the International Monetary Fund's (IMF) fiscal austerity programs have weakened the potential for redistribution both within poor countries and between rich and poor countries. The current development paradigm's focus on "sustainability" is an obstacle to developing systems of global social protection and an impediment to future progress. Reforming IMF policy conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…MacDonald, 2007;Batniji, 2009;Ooms and Hammonds, 2009;Rowden, 2009;Stuckler and Basu, 2009;Baker, 2010). Moreover, wage ceilings, particularly in the health sector -that is, limits on the amount that a government can spend on wages -prevent desirable increases in health employment.…”
Section: Imf-supported Programmes and Socialmentioning
confidence: 99%
“…MacDonald, 2007;Batniji, 2009;Ooms and Hammonds, 2009;Rowden, 2009;Stuckler and Basu, 2009;Baker, 2010). Moreover, wage ceilings, particularly in the health sector -that is, limits on the amount that a government can spend on wages -prevent desirable increases in health employment.…”
Section: Imf-supported Programmes and Socialmentioning
confidence: 99%
“…In relation to health, the IMF has long been criticized for impeding the development of public health systems (Baker, 2010;Batniji, 2009;Benson, 2001;Benton & Dionne, 2015;Cornia, Jolly, & Stewart, 1987;Goldsbrough, 2007;Kentikelenis, King, McKee, & Stuckler, 2015; Kentikelenis, Stubbs, & King, 2015;Ooms & Hammonds, 2009;Stuckler, Basu, & McKee, 2011;Stuckler, King, & Basu, 2008;Stuckler & Basu, 2009). For example, a recent qualitative analysis of IMF programmes in Guinea, Liberia, and Sierra Leone found that the organization contributed to the failure of health systems to develop, thereby exacerbating the Ebola crisis (Kentikelenis et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Major funders can have a significant impact on overall financial flows; International Monetary Fund (IMF) economists are advising that countries divert aid to reserves because of concerns about its unreliable and unpredictable nature, and the desire to privatize health care services rather than perpetuate state-run health care operations [74],[75]. A recent study found that when countries are borrowing from the IMF more than 98% of aid is diverted to reserves or displacing government spending on health [75].…”
Section: Discussionmentioning
confidence: 99%